Analisis Kesehatan Mental Pelajar di Era Pembelajaran Digital - Putri Masayu Asahri; Sartono Sartono (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Technological development has brought significant changes to the world of education, notably through the implementation of digital learning systems. However, these changes have also significantly impacted students' mental health. This research aims to analyze various factors affecting students' mental health in the digital learning era and to identify their impacts. This study employs a Systematic Literature Review (SLR) methodology using various published journals. Analysis was conducted using Huber and Miles' interactive analysis model. The results reveal that high academic workload, lack of social interaction, technology dependence, inequitable learning access, and limited emotional support are the main factors affecting students' mental health. Common impacts include academic stress, anxiety, mild to severe depression, digital fatigue, and physical health disorders. Therefore, collaborative efforts from students, families, educational institutions, and government are needed to create a healthy digital learning system.